T cell responses against microsatellite instability-induced frameshift peptides and influence of regulatory T cells in colorectal cancer - Bauer, Kathrin; Nelius, Nina; Reuschenbach, Miriam; Koch, Moritz; Weitz, Jürgen; Steinert, Gunnar; Kopitz, Jürgen; Tariverdian, Mirjam; Knebel Doeberitz, Magnus von; Kloor, Matthias (Cancer immunology immunotherapy, 2013)
High-level microsatellite-unstable (MSI-H) colorectal carcinomas (CRC) represent a distinct subtype of tumors commonly characterized by dense infiltration with cytotoxic T cells, most likely due to expression of MSI-H-related frameshift peptides (FSP). The contribution of FSP and classical antigens like MUC1 and CEA to the cellular immune response against MSI-H CRC had not been analyzed so far. We analyzed tumor-infiltrating and peripheral T cells from MSI-H (n = 4 and n = 14, respectively) and microsatellite-stable (MSS) tumor patients (n = 26 and n = 17) using interferon gamma ELISpot assays. Responses against 4 FSP antigens and peptides derived from MUC1 to CEA were compared with and without depletion of regulatory T cells, and the results were related to the presence of the respective antigens in tumor tissue. Preexisting FSP-specific T cell responses were detected in all (4 out of 4) tumor-infiltrating and in the majority (10 out of 14) of peripheral T cell samples from MSI-H CRC patients, but rarely observed in MSS CRC patients. Preexisting T cell responses in MSI-H CRC patients were significantly more frequently directed against FSP tested in the present study than against peptides derived from classical antigens MUC1 or CEA (p = 0.049). Depletion of regulatory T cells increased the frequency of effector T cell responses specific for MUC1/CEA-derived peptides and, to a lesser extent, T cell responses specific for FSP. Our data suggest that the analyzed FSP may represent an immunologically relevant pool of antigens capable of eliciting antitumoral effector T cell responses.